HPB P09 Forgotten ERCP Stents: Is a National Registry Required. (7th December 2022) - Clements, Caterina; Bezzaa, Sabrina; Curwen, Oliver; Kersey, James; Nehra, Dhiren; Jamal, Karim; Lewis, Trystan
Abstract: Background: Pre-operative endoscopic retrograde cholangiopancreatography (ERCP), stone removal and interval cholecystectomy is the widely practiced management for choledocholithiasis with concomitant gallstones. Biliary stenting is performed with plastic or metallic stents which require removal after 3–6 months. The sequelae from the forgotten biliary stent following laparoscopic cholecystectomy, stent occlusion, migration or cholangitis, carry significant morbidity and cost implications. Methods: Pre-operative endoscopic retrograde cholangiopancreatography (ERCP), stone removal and interval cholecystectomy is the widely practiced management for choledocholithiasis with concomitant gallstones. Biliary stenting is performed with plastic or metallic stents which require removal after 3–6 months. The sequelae from the forgotten biliary stent following laparoscopic cholecystectomy, stent occlusion, migration or cholangitis, carry significant morbidity and cost implications. Results: 308 laparoscopic cholecystectomies were performed in the study period. 25 (8%) underwent pre-operative biliary stenting, of these 16 underwent successful stent removal. 7 patients are still awaiting removal and 2 were discharged without stent removal and lost to follow up. One of these required emergency admission and removal of the stent at a tertiary centre due to stent complication. The average time from biliary stenting with ERCP to cholecystectomy was 99 days. The average time from cholecystectomy to removal of biliary stents was 113 days. The average length of time from insertion of biliary stent to removal was 195 days. Conclusions: Where common bile duct exploration at the time of cholecystectomy is not possible we recommend ERCP units provide a stent registry system with a deadline for biliary stents in the registry system for each patient.